Recent updates in click and computational chemistry for drug discovery and development - Cai, Jiang Hong; Zhu, Xuan Zhe; Guo, Peng Yue; Rose, Peter; Liu, Xiao Tong; Liu, Xia; Zhu, Yi Zhun (Frontiers in Chemistry, 2023)
Drug discovery is a costly and time-consuming process with a very high failure rate. Recently, click chemistry and computer-aided drug design (CADD) represent popular areas for new drug development. Herein, we summarized the recent updates in click and computational chemistry for drug discovery and development including clicking to effectively synthesize druggable candidates, synthesis and modification of natural products, targeted delivery systems, and computer-aided drug discovery for target identification, seeking out and optimizing lead compounds, ADMET prediction as well as compounds synthesis, hopefully, inspires new ideas for novel drug development in the future.